TINJAUAN YURIDIS SERTIFIKASI HALAL DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN (STUDI PRODUK MAKANAN HASIL OLAHAN USAHA MIKRO DAN KECIL DI KOTA PONTIANAK) - NIM. A1012201019, IRMA WULANDARI (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractIn this era, distinguishing between halal and haram food is not easy. This research aims to examine the basis of the relationship between halal certification of food products processed by micro and small businesses. Furthermore legal protection for consumers and to assess the work of halal certification of food products processed by micro and small businesses in protecting consumers in Pontianak City.The types of studies used is normative juridical, with a conceptual approach and a statutory approach. This research seeks to examine certain legal issues based on primary and secondary data. Data collection techniques use observation, interviews, and documentation techniques. Next, the research results are described in detail in sentence form so that conclusions can be drawn.The study of halal certification and legal protection for Muslim consumers for food products processed by micro and small businesses is interconnected due to several reasons, including: first, that the majority of consumers are Muslims who should receive certainty regarding the products offered, circulated, and traded by business actors, so that Islamic principles for guaranteeing halal products must be considered and taken seriously. Second, halal certification and consumer protection are citizen